APLIKASI DUKUNGAN KELUARGA DALAM MENINGKATKAN KEPATUHAN DIET PENDERITA DENGAN DIABETES MELITUS DI WILAYAH KERJA RT 04 KELURAHAN PULOKERTO - Lela Aini; Lenny Astuti; Setiawan; Dewi Rury Arindari; Shinta Maharani; Dea Mega Arini; Sri Mulia Sari; Latifah (Ukhuwah : Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACK In line with the change of era and the increased number of people, the increase of people with Diabetes Mellitus (DM) is quite high, such increase of DM case is potentially caused by the transformation of lifestyle and dietary program (Pakaya, 2023). Some External factors in the prevention of Diabetes Mellitus include the interaction of health workers with patients, environmental aspects and family support. (Hamdani et al., 2017). This community service activity aims to inform and educate the respondents about the application of family support in improving dietary compliance of patients with diabetes mellitus around RT 04 Pulokerto Village. This activity was done on November 12th, 2024 at Pulokerto Village, Gandus District Palembang with 35 participants. This activity was kind of community empowerment through health counseling by lecturing and discussion methods. The material contains the application of family support in improving the dietary compliance of patients with diabetes mellitus around RT 04 Pulokerto Village. It is hoped that the community could enrich the information about diabetes mellitus dietary adherence by attending regular counseling activities from health practitioners. Keywords: Diabetes Mellitus, Dietary Obedience, Family Support.